2020
DOI: 10.1007/s00192-019-04200-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pessary cleaning and optimal time interval for follow-up: a prospective cohort study

Abstract: Introduction and hypothesis The objective of this study was to determine the efficacy of routine follow-up visits for pessary cleaning, the effect of extended time intervals between visits and the proportion of patients being able to self-manage their pessary for pelvic organ prolapse (POP). Methods We conducted a prospective cohort study in patients with a stage ≥II POP without previous POP surgery. All patients received a pessary as primary treatment. Our main outcome measure was a difference ≥2 in median vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…A prospective cohort study determined the efficacy of routine follow-up visits for pessary cleaning at 3 and 9 months after insertion. They concluded that frequent pessary cleaning in asymptomatic women is not efficient, and there is no difference in the severity of the pessary-related adverse effects between a 3- and a 9-monthly follow-up interval [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort study determined the efficacy of routine follow-up visits for pessary cleaning at 3 and 9 months after insertion. They concluded that frequent pessary cleaning in asymptomatic women is not efficient, and there is no difference in the severity of the pessary-related adverse effects between a 3- and a 9-monthly follow-up interval [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective cohort following 163 ring pessaries found no difference in pain, discharge, or irritation when the interval of cleaning was increased to 9 months. They also reported that 45.2% were able to manage self-cleaning for the directed period of time [21].…”
Section: Pessary Managementmentioning
confidence: 99%
“…Seven studies provided data on risk of adverse events with long-term pessary use (without removal or cleaning) [17][18][19][20][21][22][23]. Nine additional articles were reviewed that provided information of interest during the pandemic [24][25][26][27][28][29][30][31][32].…”
Section: Pessary Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence on pessary self-management is limited and from small non-randomised studies7891011 (table 1, supplementary file). The studies mainly report on the length of time for which women continue to use a pessary.…”
Section: What Is the Evidence Of Uncertainty?mentioning
confidence: 99%